An antisense RNA expression vector for Neurospora crassa - W. Fecke; U. Nehls; H. Weis (Fungal Genetics Reports, 1993)
The artificial expression of antisense RNA is commonly used in eucaryotes, especially higher plants, to reduce the level of specific proteins (van der Krol et al. 1988 Nature 333:866-869). Here we report the use of antisense RNA to inhibit the translation of a subunit of the mitochondrial NADH:ubiquinone oxidoreductase, the respiratory complex I in N. crassa